Joseph Wauters - Masy, Sylvain; Vandervelde, Emile (Liège : Coop Typo-Litho, 1937)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: Wauters, Joseph; socialistische arbeidersbeweging; Borgworm; Huy; Hoei